2007
DOI: 10.1080/13550280701549417
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus infection inhibits granulocyte-macrophage colony-stimulating factor–induced microglial proliferation

Abstract: It is well known that infection by the human immunodeficiency virus (HIV) dysregulates cell physiology, but little information is available on the consequences of HIV infection in primary macrophages and microglia. The authors examined the relationship between cell proliferation and HIV infection in primary cultures of microglia and in human central nervous system (CNS). In cultures infected with HIV (ADA and BaL), granulocyte-macrophage colony-stimulating factor (GM-CSF)-mediated cell proliferation was reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…GM‐CSF and macrophage colony‐stimulating factor are principal microglial growth factors; their expression (along with that of their cognate receptors) is upregulated in the injured or diseased CNS [Giulian and Ingeman, ; Raivich et al, ; Lee et al, ; Cosenza‐Nashat et al, ]. Here, GM‐CSF levels were slightly lower in sera from TBE patients than in that from control subjects, which is puzzling and requires further study.…”
Section: Discussionmentioning
confidence: 91%
“…GM‐CSF and macrophage colony‐stimulating factor are principal microglial growth factors; their expression (along with that of their cognate receptors) is upregulated in the injured or diseased CNS [Giulian and Ingeman, ; Raivich et al, ; Lee et al, ; Cosenza‐Nashat et al, ]. Here, GM‐CSF levels were slightly lower in sera from TBE patients than in that from control subjects, which is puzzling and requires further study.…”
Section: Discussionmentioning
confidence: 91%
“…HIVE sections for study were chosen based on the presence of multinucleated giant cells (MGCs) and microglial nodules on haematoxylin and eosin (H&E) and/or presence of HIV gag p24 expression by IHC. The details with regards to age and sex for all but one of the cases from the NNTC have been previously reported [23,24]. The additional section (case 38) was from a 47‐year‐old black woman.…”
Section: Methodsmentioning
confidence: 99%
“…This study focuses on the preventive measures taken by the microglia to contain viral replication within the CNS. It was further observed that the infection with Vpr mutant virus did not arrest this GMCSF induced proliferation indicating a role of this protein in maintaining HIV reservoirs upon suppression of host cell proliferation (59).…”
Section: Human Immunodeficiency Virus-1 (Hiv-1)mentioning
confidence: 98%
“…In a study carried out by Cosenza-Nashat et. al., Granulocyte Macrophage Colony Stimulating Factor (GMCSF), which elevates during HIV-1 infection within the CNS, reduces the proliferation of productively infected primary microglia by arresting them in the G1/M phages of the cell cycle at least in vitro (59). This study focuses on the preventive measures taken by the microglia to contain viral replication within the CNS.…”
Section: Human Immunodeficiency Virus-1 (Hiv-1)mentioning
confidence: 99%